2012
DOI: 10.1186/1743-7075-9-95
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the iron deficient metabolic response in rats fed either an AIN-76 or AIN-93 based diet

Abstract: BackgroundPrevious studies examining the metabolic consequences of dietary iron deficiency have reported elevated serum glucose concentrations in iron-deficient animals. Importantly, the majority of these findings were observed using an earlier version of a laboratory animal diet (AIN-76A) in which the primary carbohydrate source was sucrose – a disaccharide known to negatively impact both glucose and lipid homeostasis. The AIN-76A diet formula was improved in 1993 (AIN-93) to optimize animal nutrition with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…19 however a study found that altered status of iron is enough to impair homeostasis of glucose. 20 Diet and physical activity are not only aimed for weight reduction but also have a role in boosting immunity including (immune activation and immune-senescence) and metabolism (obesity, diabetes, and metabolic syndrome). 21 Consumption of fresh foods, eggs and consuming meals 3 times / day were also related to lower risk of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…19 however a study found that altered status of iron is enough to impair homeostasis of glucose. 20 Diet and physical activity are not only aimed for weight reduction but also have a role in boosting immunity including (immune activation and immune-senescence) and metabolism (obesity, diabetes, and metabolic syndrome). 21 Consumption of fresh foods, eggs and consuming meals 3 times / day were also related to lower risk of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies, in the moderate in¬duction of iron deficiency in ro¬dents are sufficient to disrupt normal metabolic homeostasis, to cause glucose and insulin elevations in both steady-state levels with the basal diet for-mulation in the IDanimals. High cortisol secretion, the secondary of the stress of anemia status, is not responsible for the hyperglycemia, while hyperglycemia was associated with de¬crease cortisol levels in the ID-animals [104][105][106][107][108][109].…”
Section: Iron Deficiency and Diabetes Riskmentioning
confidence: 92%
“…However, in the non-severe hemoglobin reductions are not correlated with hyperglycemia and hyperlipidemia. These findings may suggest that these may have a certain threshold exists in order to develop these potentially negative meta¬bolic consequences [103][104][105][106]. However, other studies, in the moderate in¬duction of iron deficiency in ro¬dents are sufficient to disrupt normal metabolic homeostasis, to cause glucose and insulin elevations in both steady-state levels with the basal diet for-mulation in the IDanimals.…”
Section: Iron Deficiency and Diabetes Riskmentioning
confidence: 95%
“…Ulva polysaccharides conjugated with iron ions can effectively rescue mice from artificially induced anemia [165]. Moreover, Ulva polysaccharides-iron molecules raised B and T cell levels to a number comparable to control animals [166].…”
Section: Superfoods As Nutritional Strategies For Iron Level Replenismentioning
confidence: 95%